Sustainable Agricultural Production in Africa: The Roles of Finance and Investments - Tetteh, M. L. (University of Ghana, 2025)
Agriculture, a vital contributor to the socio-economic well-being of African nations, is facing increasing environmental uncertainty. Therefore, substantial financing and investments are required to adapt to current conditions and mitigate future risks. This thesis explores the potential of various financing and investments to foster environmentally sustainable and resilient agricultural production in Africa. It consists of four empirical chapters that offer crucial insights to inform policy and practice in the field. The first empirical chapter examined the green efficiency of agricultural production using the slacks-based measure data envelopment analysis with the undesirable outputs approach. Our findings reveal that Africa's agricultural sector exhibits an estimated average green efficiency score of 66%. Unsustainable input intensification involving arable land, fertiliser, irrigation water, and pesticides were identified as the primary source of the inefficiency. Our study shows the exact optimal levels of input usage and emission reductions required to address the identified inefficiencies. The second empirical chapter examined the impact of financial investments and agri environmental fiscal policies (fiscal policies that promote environmental sustainability in agricultural production) on African climate-smart agriculture in a two-stage approach. The first stage relied on the slacks-based measure data envelopment analysis with the undesirable outputs approach. At the second stage, we applied the fractional heteroscedasticity probit model to estimate the influencing factors of agricultural green efficiency (optimising agricultural output without harming the environment). Our findings show that investments in agricultural technology and prudent capital expenditure can enhance green efficiency. Financial aid to agriculture is a crucial driver of green productivity, and climate financing can be adequate when implemented through agri-environmental fiscal policies. Carbon-related fiscal policies were found to have a positive impact on green productivity, while methane related policies yielded mixed results. Interestingly, urbanisation threatens green efficiency, while environmental management and eco-vitality promote sustainable productivity. In the third empirical chapter of the thesis, we studied the dynamic interconnections between agriculture output value, domestic credit, foreign direct investment in agriculture, food price variation, and sustainable agriculture practices using the panel vector autoregression methodology. The empirical results demonstrate statistically significant interdependence among all the variables, with a one-way transmission effect of agriculture output value to domestic credit, FDI, and sustainable farming practices. Additionally, bi-directional causality is established between food price anomalies and output value, FDI and domestic credit, and FDI and sustainable farming practices. The final empirical chapter analysed the influence of research and development (R&D) expenditure and globalisation on agriculture value-added in Africa. The chapter applied the dynamic common-corrected effects mean group and local projection estimators as estimation techniques. The empirical evidence shows that R&D investments positively influence agriculture value-added in the medium to long term. However, globalisation has yet to significantly impact agriculture value-added in Africa except through financial development synergies requiring a continued and consistent R&D investment and a definite globalisation strategy.
PhD. Finance
Keywords: Agriculture; Green Efficiency; Agricultural Finance; Sustainable Agricultural Finance; Sustainable Fiscal Policies